Income allocation of selected household helpers in Metro Manila - Hizon, Tracy K.; De Guzman, Ines A. (Quezon City College of Home Economics, University of the Philippines Diliman, 2012)
Employing domestic help has been a part of the Filipino culture. Household helpers in the Philippines receive a monthly income of Php 1,500.00 to Php 3,000.00 for working in rural and urban areas respectively (Reyes, 2009). The study aimed to describe the income allocation of household helpers for personal and left behind families' expenditures and personal savings, to determine the relationship between monthly income and expenditures and savings, to identify the problems and solutions encountered by household helpers in allocation of income and determine the sufficiency of household helper's monthly income. The female household helpers who were respondents of the study were selected through convenience sampling. Data collection was done through survey interview and frequency distribution and percentages were used for data analysis. Pearson's r test was used to show the correlation between the respondents' monthly income and expenditures and savings using the significance level .05. Results show that many helpers allocate more for left behind families, less for themselves and nothing for personal savings. Also, as the monthly income of household helpers increases, their expenditure also increase. Their main problem was lack of money and they usually solve it by borrowing from their employers. Based on the current and proposed minimum wage, the household helpers' monthly income is said to be sufficient, but because they also provide for their left behind families, many of the respondents found their salaries insufficient.
Thesis (BS Home Economics)--University of the Philippines Diliman
Keywords: Domestic helpers -- Philippines; Income distribution